Monitoring and Evaluating Climate Resilient Investment Projects: Strengthening Capacities under the FLLoCA Program - Jalango, Dorcas Anyango; Binge, Brenda Binge; Njuguna, Lucy Wanjiku (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
This info note reviews Kenya’s Financing Locally Led Climate Action (FLLoCA) program and the effort to strengthen monitoring, evaluation, and learning (MEL) for climate-resilient investments. It outlines the financing architecture and KfW’s EUR 31 million support to 16 western counties, emphasizing a harmonized results framework that links county projects to national outcomes. Two cross-cutting KPIs, that is; sustainable land use and job creation (with a focus on women and youth) guide performance tracking. Drawing on Alliance Bioversity & CIAT experience with the CSA Investment Plan MEL framework and the Adaptation Tracking Tool, partners co-developed a streamlined MEL framework that will be piloted within FLLoCA counties, through training officials to enable transparent, evidence-based reporting and more resilient local investments.